1996
DOI: 10.1007/s002689900144
|View full text |Cite
|
Sign up to set email alerts
|

Mortality following Lower Limb Ischemia‐Reperfusion: A Systemic Inflammatory Response?

Abstract: Restoration of blood flow to an acutely ischemic lower limb may paradoxically result in systemic complications and unexpected mortality. It has been suggested that lower limb ischemia reperfusion alters gut permeability. In this study, using a rat model, we determined the effect of acute lower limb ischemia-reperfusion on mortality rate, bowel morphology, and circulating concentrations of endotoxin and the proinflammatory cytokine interleukin-6. Survival rate was compared in two groups of adult Wistar rats: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 35 publications
3
37
1
3
Order By: Relevance
“…Cohen et al [13] reported that all rats subjected to 2 h of lower torso ischemia by cross-clamping of the infrarenal aorta followed by reperfusion died within 12 h of pulmonary, hepatic, and renal injuries. Yassin et al [15] have reported that in rats subjected to 3 h of bilateral hindlimb ischemia followed by reperfusion, the mortality rates were 50% within 24 h and 70% within 72 h. It is desirable to reduce the cross-clamp time to prevent death of the experimental animals.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cohen et al [13] reported that all rats subjected to 2 h of lower torso ischemia by cross-clamping of the infrarenal aorta followed by reperfusion died within 12 h of pulmonary, hepatic, and renal injuries. Yassin et al [15] have reported that in rats subjected to 3 h of bilateral hindlimb ischemia followed by reperfusion, the mortality rates were 50% within 24 h and 70% within 72 h. It is desirable to reduce the cross-clamp time to prevent death of the experimental animals.…”
Section: Discussionmentioning
confidence: 97%
“…In this model, the aorta is cross-clamped and the lower torso is not perfused while a segment of aorta is infused with elastase. Ischemia-reperfusion of the lower torso produces various chemical mediators [13,14] such as arachidonic acid metabolites and proinflammatory cytokines, the presence of which results in systemic inflammation [13,15]. Cohen et al [13] reported that all rats subjected to 2 h of lower torso ischemia by cross-clamping of the infrarenal aorta followed by reperfusion died within 12 h of pulmonary, hepatic, and renal injuries.…”
Section: Discussionmentioning
confidence: 98%
“…Reperfusion injury develops on remote organs such as lungs, heart, liver, and kidneys that threatening life and makes progress acute renal and respiratory failure, cardiac dysfunction, and even death resulting from systemic toxic effects of reperfusion products known as myonephropathic-metabolic syndrome [18][19][20] . Yassin et al 21 explained that the restoration of blood flow to an acutely ischemic lower limb in rats may, paradoxically, result in systemic complications and unexpected mortality. There was a significant increase in plasma concentrations of urea, creatinine, aspartate transaminase, alanine transaminase, and lactic dehydrogenase in reperfused animals compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle ischemia-reperfusion is associated with a systemic inflammatory response and determines the effect on remote organs (lung, liver, and kidney) structure and function 1,2 . It is well known that interactions between the blood elements and the vascular endothelium are responsible for the reperfusion injury: endothelial injury with swelling and lysis due to loss of ionic and osmotic gradients, loss of vasoregulatory control, diminished of the endotheliumderived vasodilator nitric oxide, polymorph nuclear leukocytes (PMN) activation and subsequent release of lytic enzymes leading to tissue damage 1,2 . The development of remote organ dysfunction was observed only following reperfusion, which implies that humoral and/or cellular mediators produced locally in the limb were responsible for mediating remote organ injury 3,4 .…”
Section: Introductionmentioning
confidence: 99%